Religion and public policy : human rights, conflict, and ethics / edited by Sumner B. Twiss, Marian Gh. Simion, Rodney L. Petersen. - Twiss, Sumner B.; Simion, Marian Gh; Petersen, Rodney Lawrence (Cambridge University Press, 2015)
This book pivots around two principal concerns in the modern world: the nature and practice of human rights in relation to religion, and the role of religion in perennial issues of war and peace. It articulates a vision for achieving a liberal peace and a just society firmly grounded in respect for human rights, while working in tandem with the constructive roles that religion can play even amid cultural difference. It explores topics including the status and justification of human rights; the meaning and significance of religious liberty; whether human rights protections ought to be extended to other species; how the comparative study of religious ethics ought to proceed; and the nature, limits, and future development of just war thinking. Featuring a group of distinguished contributors, this is a distinctive contribution that shows a multifaceted and original exploration of cutting edge issues with regards to the aforementioned themes.